2002
DOI: 10.1016/s0306-4522(01)00531-0
|View full text |Cite
|
Sign up to set email alerts
|

Two α2-adrenergic receptor subtypes, α2A and α2C, inhibit transmitter release in the brain of gene-targeted mice

Abstract: alpha(2)-Adrenergic receptors play an essential role in regulating neurotransmitter release from sympathetic nerves and from adrenergic neurons in the CNS. However, the role of each of the three highly homologous alpha(2)-adrenergic receptor subtypes (alpha(2A), alpha(2B), alpha(2C)) in this process has not been determined unequivocally. To address this question, the regulation of norepinephrine and dopamine release was studied in mice carrying deletions in the genes encoding the three alpha(2)-adrenergic rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
114
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(119 citation statements)
references
References 31 publications
4
114
0
1
Order By: Relevance
“…In the absence of a 2A -AR, or during pharmacological blockade of all a 2 -AR subtypes with an antagonist, the NE stores in noradrenergic neurons are susceptible to depletion by D-amph. This corroborates the evidence from a 2 -AR subtype-deficient mice revealing the principal role of the a 2A -AR in regulating the stimulation-induced NE release in cortical and hippocampal slices in vitro Trendelenburg et al, 1999Trendelenburg et al, , 2001Scheibner et al, 2001;Bücheler et al, 2002) and in the prefrontal cortex in vivo . Furthermore, the observed contribution of the a 2 -ARnoradrenergic system to modulation of the effects of D-amph is in good agreement with two earlier extensive studies on genetically modified mice, reporting increased sensitivity to psychostimulants when the brain NE homeostasis is disturbed, that is, in mice lacking the NE transporter (Xu et al, 2000) or incapable of synthesizing NE (Weinshenker et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the absence of a 2A -AR, or during pharmacological blockade of all a 2 -AR subtypes with an antagonist, the NE stores in noradrenergic neurons are susceptible to depletion by D-amph. This corroborates the evidence from a 2 -AR subtype-deficient mice revealing the principal role of the a 2A -AR in regulating the stimulation-induced NE release in cortical and hippocampal slices in vitro Trendelenburg et al, 1999Trendelenburg et al, , 2001Scheibner et al, 2001;Bücheler et al, 2002) and in the prefrontal cortex in vivo . Furthermore, the observed contribution of the a 2 -ARnoradrenergic system to modulation of the effects of D-amph is in good agreement with two earlier extensive studies on genetically modified mice, reporting increased sensitivity to psychostimulants when the brain NE homeostasis is disturbed, that is, in mice lacking the NE transporter (Xu et al, 2000) or incapable of synthesizing NE (Weinshenker et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…The decreased DOPAC formation, reflecting reduced intraneuronal metabolism of DA resulting from reuptake blockade of DA by Damph, thus, is not affected by a 2A -AR. On the contrary, the formation of HVA occurs mainly extracellularly, and the elevated HVA concentrations of a 2A -KO mice may therefore represent increased DA release in the absence of a 2A -AR heteroreceptor-mediated inhibition (Bücheler et al, 2002). Supporting this view, the HVA levels of WT mice after combined Ati-D-amph treatment were elevated to the level observed in a 2A -KO mice after D-amph alone, except in the striatum, where the a 2C -AR subtype predominates.…”
Section: Discussionmentioning
confidence: 99%
“…a-2 adrenergic agonists and fear conditioning M Frances Davies et al fear encoding (Bucheler et al, 2002). Indeed, we have found that a 2A AR-deficient mice exhibit a higher level of freezing than controls in the discrete test (Davies et al, 2003).…”
Section: Discussionmentioning
confidence: 74%
“…Noradrenergic neurons within the nucleus tractus solitarius (NTS) project to the central nucleus (Asan, 1998), and the activation of the NTS (Zardetto-Smith and Gray, 1990) contributes to an increased norepinephrine release in the amygdala and enhances memory (Williams et al, 2000). Norepinephrine release from the ascending noradrenergic tracts is also under presynaptic control of both a 2C and a 2A ARs (Bucheler et al, 2002), where they act as an autoreceptors on noradrenergic terminals. The absence of a 2A AR-mediated presynaptic inhibition in a 2A ARÀdefi-deficient mice would likely promote a stronger release of norepinephrine evoked by the US to promote discrete cue On day 1 wild-type mice were either injected with saline or dexmedetomidine (20 mg/kg i.p.)…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, mice that are homozygous for a 2C gene deletion or overexpression are viable and have been reasonably well-characterized. Overall, both strains of mouse confirm that a 2C is not responsible for the classical effects of non-selective a 2 -adrenoceptor agonists (see Kable et al, 2000), although the subtype does have some influence on neurotransmitter release (Bucheler et al, 2002;Zhang and Ordway, 2003), even if less so than does a 2A (Bucheler et al, 2002). However, the transgenic phenotypes make definition of the potential clinical applications of a 2C -selective ligands somewhat problematic.…”
mentioning
confidence: 89%